Voter Confidence in the Agricultural Industry - Eric K. Kaufman; Glenn D. Israel; Tracy A. Irani (Journal of Applied Communications, 2008)
Social scientists tend to agree that public opinion influences public policy. As the agricultural industry faces increased scrutiny from public officials and citizen advocacy groups, agricultural communication professionals are faced with the challenge of targeting messages that encourage public confidence in the industry. Research-based marketing segmentation may hold the key to effective political marketing for the industry. While some consumer research has been conducted to better understand food purchasing decisions, more is needed to better understand public attitudes toward the larger agricultural industry and to better recognize any segmentation in public opinion. This study’s findings—drawn from the Agriculture Institute of Florida’s 2006 survey, the 2000 United States Census of Population and Housing, and the 2002 United States Department of Agriculture Census of Agriculture—may help guide future industry messages toward the public.
Keywords: Social scientists; public policy; voter confidence; agricultural industry; campaigns; purchasing behaviors